2022
DOI: 10.1177/20412479221135379
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of antibacterial gels of galactomannan/ZnO nanocomposite in carbopol-based matrix using mesquite seeds as the biopolymer source

Abstract: Nanocomposite gels are novel materials mainly used in the medical field for the control drug release and distribution. In this study, the effect of the concentration of galactomannan/zinc oxide nanocomposite in a polymeric Carbopol matrix to obtain a functional nanocomposite gel was studied. The swelling, thermogravimetric, rheological, and antibacterial properties against Escherichia coli and Staphylococcus aureus were evaluated. The results indicate that there is a direct effect between the amount of the emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…18 Extensive research has been conducted in this field, as demonstrated by the work of Bouttier-Figueroa et al (2023), who synthesised nanocomposites using naturally derived polymers such as galactomannan. 18 Additionally, these works often encounter situations that agricultural hydrogels have. Such as the increased concentration of nanocomposites improving mechanical properties, but reducing the swelling due to increased network interactions, increased rigidity; reducing the matrixes polar group interactions with water, and Van der Waals interactions between the nanocomposite and the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…18 Extensive research has been conducted in this field, as demonstrated by the work of Bouttier-Figueroa et al (2023), who synthesised nanocomposites using naturally derived polymers such as galactomannan. 18 Additionally, these works often encounter situations that agricultural hydrogels have. Such as the increased concentration of nanocomposites improving mechanical properties, but reducing the swelling due to increased network interactions, increased rigidity; reducing the matrixes polar group interactions with water, and Van der Waals interactions between the nanocomposite and the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…2,9,10 A gel is a semisolid that is defined as a substantially dilute crosslinked system that does not exhibit flow when in a steady state. 11…”
Section: Introductionmentioning
confidence: 99%
“…12 Galactomannan is described as the primary chain of β –D–mannopyranose units joined by glycosidic bonds (1→4), one-third of which have side groups of single-bonded D-galactopyranose units (1→6). 11,13,14 Galactomannans are classified by their functional properties as stabilizers, thickeners, and emulsifiers. 15 Aqueous TG solutions present dilatant behavior at dilute concentrations and pseudoplastic behavior at semidiluted concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels, which are three-dimensional polymer networks characterized by high hydrophilicity and unique ability to imitate human tissues, 11 are known for their multiple biomedical applications, for instance, tissue engineering, 1214 controlled drug delivery 1517 sensors 18,19 and wound dressings. 20,21 Hydrogels based on polymers from natural, synthetic, and semi-synthetic origin or blends of the above are also commonly used as matrices in scaffold-based 3D cancer models.…”
Section: Introductionmentioning
confidence: 99%